True Affordability. Critiquing the International Housing Affordability Survey. - Litman, Todd (My University, 2020)
Many lower- and moderate-income households spend more on housing and transportation than considered affordable. When families cannot afford food or healthcare, the real reason is generally excessive housing and transport cost burdens. This harms families and communities. As a result, there is considerable interest in tools for evaluating unaffordability problems and potential solutions.The Demographia International Housing Affordability Survey (IHAS) rates regional housing affordability using Median Multiples (the ratio of median house prices to median incomes), and uses the results to advocate for urban expansion.It is heavily promoted and receives significant media attention.This study critically evaluates the IHAS methods and recommendations. It identifies significant problems. By ignoring transportation and infrastructure costs the IHAS exaggerates the affordability of urban-fringe housing, and undervalues compact infill. It blames housing unaffordability on urban containment regulations, although they are uncommon and increase housing prices less than regulations that limit infill. It ignores many sprawl costs and Smart Growth benefits. The IHAS fails to reflect professional standards: its methods are incomplete and outdated, it misrepresents key research, is not transparent, and lacks peer review. This indicates that the IHAS is intended to support a political agenda rather than provide objective guidance. Although the IHAS information maybe useful, it is important that users understand its biases.
Keywords: Wohnkosten; Lebenshaltungskosten; Messung; Haushaltseinkommen; Datenerhebung; Infrastrukturentwicklung; Beförderungskosten